Determinants of the type of health care sought for symptoms of Acute respiratory infection in children: analysis of Ghana demographic and health surveys - Leslie Danquah; Prince Michael Amegbor; Dawit Getnet Ayele (BMC, 2021)
Abstract Background Globally, acute respiratory infection (ARI) is a leading cause of infant and childhood morbidity and mortality. Currently, it is estimated that 50 million cases of childhood ARI are untreated. In this study, we identified determinants of the type of treatment sought for symptoms of childhood acute respiratory infection (ARI), including non-treatment, amongst a nationally representative sample of children under five years in Ghana. Methods In total, 1 544 children were studied by a secondary analysis of pooled survey data from the 1993, 1998, 2003, 2008, and 2014 Ghana Demographic and Health Surveys (GDHS). Cross-tabulations, chi-square, multinomial logistic regression, and Bayesian hierarchical spatial logistic regression analyses were used to identify relationships between the type of treatment sought and maternal socio-economic and household characteristics. Results Seeking medical care was significantly associated with child age (RRR= 1.928, 95 % CI 1.276 - 2.915), maternal employment status (RRR = 1.815, 95 % CI 1.202 - 2.740), maternal health insurance status, (RRR = 2.618, 95 % CI 1.801 - 3.989), children belonging to middle (RRR = 2.186, 95 % CI 1.473 - 3.243), richer (RRR = 1.908, 95 % CI 1.145 - 3.180) and richest households (RRR = 2.456, 95 % CI 1.363 - 4.424) and the 1998 survey period (RRR = 0.426, 95 % CI 0.240 - 7.58). Seeking self-care or visiting a traditional healer was significantly associated with maternal educational status (RRR = 0.000, 95 % CI 0.000 - 0.000), and the 1998 (RRR= 0.330, 95 % CI 0.142 - 0.765), 2003 (RRR= 0.195, 95 % CI 0.071 - 0.535), 2008 (RRR= 0.216, 95 % CI 0.068 - 0.685) and 2014 (RRR= 0.230, 95 % CI 0.081 - 0.657) GDHS periods. The probability that the odds ratio of using medical care exceeded 1 was higher for mothers/caregivers in the Western, Ashanti, Upper West, and Volta regions. Conclusions Government policies that are aimed at encouraging medical care-seeking for children with ARI may yield positive results by focusing on improving maternal incomes, maternal NHIS enrolment, and maternal household characteristics. Improving maternal education could be a positive step towards addressing challenges with self-care or traditional healing amongst children with ARI.